Increased risk of asthma in overweight children born large for gestational age. Issue 8 (28th July 2017) - Pinto, L. A.; Guerra, S.; Anto, J. M.; Postma, D.; Koppelman, G. H.; de Jongste, J. C.; Gehring, U.; Smit, H. A.; Wijga, A. H.
Summary: Background: Being born large for gestational age (LGA) is a marker of increased growth velocity in fetal life and a risk factor for childhood overweight. Both being born LGA and childhood overweight may influence the development of asthma, although the role of overweight in the association between LGA and childhood asthma is unclear. Importantly, recent studies have suggested that the association between overweight and asthma may be related to non‐allergic pathways. If this also applies to the association between LGA and asthma, the association between being born LGA and asthma may be different for atopic and non‐atopic children. Objective: We investigated the association of being LGA with the prevalence of asthma at age 8 in atopic and non‐atopic children and the role of overweight in this association. Methods: Complete data on asthma, anthropometry and atopy at age of 8 years, and potential confounders were available for 1608 participants of the PIAMA birth cohort. Odds ratios for the association between LGA and asthma in atopic and non‐atopic children were estimated by logistic regression analysis adjusting for potential confounders. Overweight was assessed as a potential modifier of the association between LGA and asthma. Results: Being born LGA was not significantly associated with asthma at age of 8 in atopic and non‐atopic children. However, overweight at age of 8 years modified the association between asthma at age of 8 and LGA. In non‐atopic children, children who were born LGA and were overweight at age of 8 years had a significantly increased odds of asthma compared to non‐LGA, non‐overweight children (adj OR 7.04; 95% CI 2.2‐24). Conclusions: We observed that non‐atopic children born LGA, who were overweight by 8 years have an increased risk of asthma. If confirmed, these findings suggest that non‐atopic children born LGA may be identified early in life as a high‐risk group for asthma.